Unveiling the noncanonical activation mechanism of CDKs: insights from recent structural studies - Li, Tao; Tang, Hui-Chi; Tsai, Kuang-Lei (Frontiers in Molecular Biosciences, 2023)
The Cyclin-dependent kinases (CDKs) play crucial roles in a range of essential cellular processes. While the classical two-step activation mechanism is generally applicable to cell cycle-related CDKs, both CDK7 and CDK8, involved in transcriptional regulation, adopt distinct mechanisms for kinase activation. In both cases, binding to their respective cyclin partners results in only partial activity, while their full activation requires the presence of an additional subunit. Recent structural studies of these two noncanonical kinases have provided unprecedented insights into their activation mechanisms, enabling us to understand how the third subunit coordinates the T-loop stabilization and enhances kinase activity. In this review, we summarize the structure and function of CDK7 and CDK8 within their respective functional complexes, while also describing their noncanonical activation mechanisms. These insights open new avenues for targeted drug discovery and potential therapeutic interventions in various diseases related to CDK7 and CDK8.